The Role of Online Atmospheric Qualities Towards Post-Purchase Regret in An Online Second-Hand Clothing Purchases (Journal of Innovation, Business and Entrepreneurship, 2020)
The advancement of technology has made it possible for second-hand products to be purchased through online retailers. However, as modern customers started to shift towards online shopping, customers are more likely to suffer post-purchase regret. Prior researchers have begun to concentrate on different aspects of the online shopping environment ever since this channel entered the commercial landscape, and found atmospheric qualities as an essential online shopping aspect. Therefore, this study aims to discover the factors that influence customer's post-purchase regret in an online second-hand fashion product purchase by considering the online atmospheric qualities. Data is collected through a semi-structured interviews and questionnaire survey. The qualitative data will be analyzed using thematic analysis, whereas to test hypothesized relationships between the variables, namely perceived quality of product-related cues, perceived quality of service-related cues, perceived enjoyment, impulse buying, and post-purchase regret, the researcher will use PLS-SEM. The findings of this research show that in an online second-hand clothing purchase context, customers have more concern towards product-related cues rather than service-related cues. Furthermore, this research also discovers that impulse buying has a direct significant positive relationship with post-purchase regret.Keywords: Second-hand clothing, atmospheric qualities, post-purchase regret